Current medical diagnosis & treatment 2007 - 4 0 16; McPhee, Stephen J.;Papadakis, Maxine A.;Tierney, Lawrence M.; 5 (New York : McGraw-Hill Medical, 2007)
A comprehensive guide to diagnoses and treatments of medical conditions that discusses approaches to patient and health maintenance, common symptoms, preoperative evaluation and management, geriatrics, end of life care, various organs, breasts, gynecology, obstetrics, different disorders, urology, endocrinology, diseases, abnormalities, poisoning, complementary and alternative medicine, and more.
Includes bibliographical references and index.
Adult;Adult
Keywords: 2 -- 0; 6; Diagnosis;Diseases;Therapeutics;Diagnosis;Diseases;Therapeutics -- Handbooks, manuals, etc.;Handbooks, manuals, etc.;Handbooks, manuals, etc.;Handbooks, manuals, etc.;Handbooks, manuals, etc.;Handbooks, manuals, etc; 20; 2